(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This paper aims to study the Baathist-Nasserist dialogue occurred in the years preceding the establishment of the United Arab Republic (1952-1958). After providing a historical overview of the evolution of Arab nationalism, this study tries to understand the mutual ideological influences and differences between Baʿathist and Nasserite terminology. In addition, it discusses the effects of such dialogue within the ideological and political context. The research relies on a thorough analysis of Arabic primary sources, from the writings of Baʿath founders to ʿAbd al-Nāṣir’s speeches and writings. Keywords such as “revolution”, “struggle”, “socialism” and “Arabism” will be analyzed and compared. By examining the most relevant conceptual issues from a linguistic and historical perspective, this paper aims to enrich the already existing field of studies about the historical and ideological reassessment of the UAR and, more broadly, of the so called “secular” pan-Arab movements.